2019
DOI: 10.21203/rs.2.10871/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ocular biomarkers for cognitive impairment in nonagenarians; a prospective cross-sectional study

Abstract: Background: Ocular imaging receives much attention as a source of potential biomarkers for dementia. In the present study, we analyze these ocular biomarkers in cognitively impaired and healthy participants in a population aged over 90 years (= nonagenarian), and elucidate the effects of age on these biomarkers. Methods: For this prospective cross-sectional study, we included individuals from the EMIF-AD 90+ study, consisting of a cognitively healthy (N=67) and cognitively impaired group (N=33), and the EMIF-A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…High‐definition optical coherence tomography (HD‐OCT) is a cost‐effective and convenient tool that allows for high‐resolution retinal images to be obtained in vivo. With the advent of OCT, the retina has become an appealing subject in many studies on neurodegenerative diseases, including AD 11–17 . However, previous OCT findings are controversial; some studies have reported a thinning of the retina in AD, 11–14 whereas others have observed no change 15–17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High‐definition optical coherence tomography (HD‐OCT) is a cost‐effective and convenient tool that allows for high‐resolution retinal images to be obtained in vivo. With the advent of OCT, the retina has become an appealing subject in many studies on neurodegenerative diseases, including AD 11–17 . However, previous OCT findings are controversial; some studies have reported a thinning of the retina in AD, 11–14 whereas others have observed no change 15–17 .…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of OCT, the retina has become an appealing subject in many studies on neurodegenerative diseases, including AD. [11][12][13][14][15][16][17] However, previous OCT findings are controversial; some studies have reported a thinning of the retina in AD, [11][12][13][14] whereas others have observed no change. [15][16][17] While there has been much interest in exploring the potential correlation between dementia and retinal parameters, there is a paucity of comprehensive and consistent data from currently available studies.…”
Section: Introductionmentioning
confidence: 99%